GEOENERGETIC FEATURES OF LANTHANOIDS AND RADIOACTIVE ELEMENTS IN IRRIGATED SOILS (Scientific journal of the Fergana State University, 2023)
The paper studies the geoenergetic features of the lanthanides and radioactive elements in the genetic horizons of irrigated meadow saz soils of Central Fergana. moreover, the number of these elements was determined depending on their geoenergetic features in the soil profile, and the geochemical Clark spectra of these elements were developed.